The Influence of HR Business Partners, Talent Mobility, and Employee Engagement on Employee Performance with the Mediation of Organizational Culture at Awal Bros Hospital, Pekanbaru - Andriani Natalia Simorangkir; Lasando Lumban Gaol (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the influence of HR Business Partners, Talent Mobility, and Employee Engagement on employee performance with organizational culture as a mediating variable at Awal Bros Hospital, Pekanbaru. This study uses a quantitative approach with a survey method by distributing questionnaires to 145 respondents who are employees from various work units. The data analysis techniques used are multiple regression and mediation test. The results show that HR Business Partners, Talent Mobility, and Employee Engagement have a positive and significant effect on employee performance. In addition, these three variables also have a significant effect on organizational culture. Organizational culture is proven to have the strongest influence on employee performance and acts as a partial mediating variable in the relationship between HR Business Partners, Talent Mobility, and Employee Engagement on employee performance. These findings indicate that human resource management practices not only directly affect performance but also through the internalization of organizational values. Theoretically, this study strengthens the relevance of Social Exchange Theory, Job Demands–Resources Model, and Resource-Based View in explaining the relationship between HR management practices, psychological factors, and employee performance. Practically, the results of this study provide implications for organizations to strengthen the role of HR Business Partners, improve talent mobility programs, encourage employee engagement, and consistently internalize organizational culture as a strategy to improve employee performance.